Penetapan Harga Di Bawah Harga Pasar Dalam Konteks Syariah: Risiko Hukum Dan Strategi Bisnis - P.Adjahum, Hanisa Amang,; Saputra, Randi Jaya; Nurhayana, Nurhayana (Fawaid : Sharia Economic Law Review, 2025)
This article discusses below-market pricing in the context of law and sharia perspective. Aggressive pricing can provide short-term profits for companies, but also presents significant legal risks, especially related to antitrust regulations and consumer protection. In this analysis, it is explained how unethical pricing practices can lead to legal sanctions and litigation from competitors. In addition, this article emphasizes the importance of understanding market dynamics and consumer behavior to avoid ongoing financial losses. The sharia perspective offers a more holistic approach by emphasizing fairness, transparency, and social responsibility in pricing. Low pricing can be considered good if it aims to provide greater access to the community, but companies must ensure the sustainability of their businesses. By involving various stakeholders in decision-making, companies can create ethical and sustainable business models that are in line with social values and applicable laws.Keywords: Pricing, Sharia Perspective, Transparency